(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Technical sciences play a critical role in driving socioeconomic development by fostering innovation, increasing productivity, and creating new industries. This article explores the multifaceted contributions of technical sciences to economic growth, focusing on technological advancements, their integration into various sectors, and their impact on job creation and societal well-being. Challenges and opportunities for maximizing the potential of technical sciences are also discussed.